Phospholipid/Bile Salt Based Novel Mixed Nanomicelles of Methotrexate Co-encapsulated with Sesamol: Preparation, Characterization, and Evaluation of Antiradical Effects In Vitro - Shaji, Jessy; Varkey, Dhanila (Current Nanomedicine, 2018)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by inflammatory activity, irreversible structural damage, and oxidative stress. Methotrexate (MTX) is widely used for RA management; however, MTX administration is associated with a decrease in the level of endogenous antioxidants. Co-administration of sesamol could combat oxidative stress alongside MTX regimen. The intent of the present study was to prepare, characterize, and evaluate the in vitro radical scavenging effects of novel mixed nanomicelles (NMs) of MTX co-encapsulated with an efficient natural antioxidant like sesamol. Methods: Novel MTX-sesamol loaded NMs (MTX-Ses-NMs) composed of phospholipid and sodium deoxycholate (SDC) were prepared by film hydration method and the micelle size, zeta potential, and entrapment efficiency (EE) was measured. Additionally, MTXSes- NMs were characterized for morphology, small-angle neutron scattering (SANS), structural features by Fourier Transform Infrared spectroscopy (FTIR), 1H nuclear magnetic resonance (NMR), and X-ray diffraction (XRD) studies. The antiradical effects of MTX-Ses-NMs were evaluated by nitric oxide (NO) radical inhibition, hydroxyl radical, and superoxide anion radical scavenging assays. Results: MTX-Ses-NMs were fabricated successfully and the micelle size and zeta potential were found to be 123 ± 76 nm and -46.8 ± 16.4 mV, respectively. The encapsulation efficiency of MTX and sesamol in MTX-Ses-NMs was found to be 89.62 ± 1.58% and 86.77 ± 1.27%, respectively. Morphology study by transmission electron microscopy (TEM), and field emission gun scanning electron microscopy (FEG-SEM) corroborates the formation of NMs. FTIR, 1H NMR, and XRD studies validate the encapsulation of MTX and sesamol within the micelle core. Analysis of SANS data confirms the presence of micelles and showed a decrease in the thickness of micelles after drug loading. Moreover, in all the antiradical assays, MTX-Ses-NMs exhibited superior radical scavenging activity as compared to free MTX. Conclusion: The rationale of co-encapsulating sesamol with MTX was to augment the antiradical effects of the developed NMs and we achieved the improved antiradical status of NMs in vitro. The novel MTX-Ses-NMs might prove beneficial in reducing the toxic effects of MTX-induced oxidative stress in vivo.
Keywords: rheumatoid arthritis